Effects of glyphosate on glyphosate-resistant maize growth and metabolic parameters in the greenhouse and field - Bidóia, Vitor Simionato [UNESP]; da Costa, Yanna Karoline Santos [UNESP]; Gratão, Priscila Lupino [UNESP]; Carbonari, Caio Antonio [UNESP]; Duke, Stephen Oscar; de Carvalho, Leonardo Bianco [UNESP] (My University, 2024)
The potential adverse effects of glyphosate on glyphosate-resistant (GR) crops are still a matter of controversy. The effects of glyphosate at recommended application rates (either a single application of 580 g ae ha−1 of glyphosate at stage V5 or a sequential application of 580 + 980 g ae ha−1 at stage V3 and V7, respectively) on growth, mineral content, and metabolic parameters of GR maize (Zea mays) were determined in greenhouse and field studies, each replicated in different years. No effects on any growth parameter (including grain yield), mineral content (leaf and grain), grain starch, crude protein, or total lipids were found. The only significant negative effect was a slight reduction in tyrosine content of leaf tissue with the sequential treatment, however, there was no increase in shikimic or quinic acids in leaf tissue with any treatment. In a separate greenhouse experiment, there was no sign of oxidative stress, as determined by levels of chlorophylls, carotenoids, and malondialdehyde (MDA) content as well as superoxide dismutase and guaiacol peroxidase activities 4 and 8 days after treatment with 1080 g ha−1 glyphosate. In fact, there was a reduction of MDA in roots of glyphosate-treated plants 4 DAT, indicating reduced oxidative stress. No aminomethylphosphonic acid, the primary degradation product of glyphosate, was found in either leaves or grain of treated plants, and no glyphosate was found in grain of treated plants from the field studies. All the results are consistent with there being no adverse effects of glyphosate on GR maize at recommended application rates.